221k views
2 votes
Here is another one if anyone can help me out

Here is another one if anyone can help me out-example-1

1 Answer

4 votes

Answer:

1. 3 × Equation [A2] --> Equation [B2]

2. 4 × Equation [B1] + Equation [B2] --> Equation [C2]

Explanation:

1. 3 × Equation [A2] --> Equation [B2]

Technically 1 x equation [A1] --> equation [B2] works, but I doubt you're meant to do that lol

Instead, this works:

4x × 3 = 12x

-7y × 3 = -21y

8 × 3 = 24

2. 4 × Equation [B1] + Equation [B2] --> Equation [C2]

(-3x × 4) + 12x = -12x + 12x = 0x

(2y × 4) + -21y = 8y - 21y = -13y

(7 × 4) + 28 = 28 + 24 = 52

=========================

I'll try to explain my process a little this time.

From A to B, you can see that equation 2 changed. Looking at the first term, 4x changed to 12x. Thats a multiplier of 3, and you can check that on the rest. In this case, that works.

Then from B to C, equation 2 changed again. This time, I noticed that x was canceled out. That means -12x had to have been added to 12x. In equation 1, theres a -3x. 4 times that is -12, and adding -12x to equation 2 works. Check that with the rest, and they all work.

User Vasudha
by
4.8k points